The gym group private equity challenge–group F capital structure, financial forecast & LBO, returns, exit strategy and due dilligence - Schroff, Jan Laurens (2020)
horoughlyanalyzedandthecompany’spositioninthemarketassessed.Inthefollowing,acomprehensiveappraisalofinfluencingfactorsonitsfinancialperformancewasconductedandgrowthdriversforecastedtocomeupwiththreedifferentcasesofhowthefirmmightdevelop.Thisknowledgewasquantifiedandthecompanysubsequentlyvaluedusingacomparablecompany,aprecedenttransaction,aDCFvaluationmethodaswellasanLBOmodel.Additionally,aninvestmentthesisandfuturestrategyregardingtheoperationsofthetargetandtheresponsibilitiesofaPEfund,suchassourcingandanexitstrategy,weredeveloped.Finally,potentialreturnswerecalculatedforthedifferentscenarios.Thethirdpartcomprisesthecapitalstructure,financialforecast,LBO,returns,exitstrategyandduediligence